The Clinical Eye: A Need to Improve the Teaching of Semiology in Undergraduate Medical Education - Carlos Jesús Toro-Huamanchumo; Carlos Jesús Toro-Huamanchumo; Laura Rosa Arce-Villalobos; Laura Rosa Arce-Villalobos (University Library System, University of Pittsburgh, 2014)
NA